Ocular abnormalities in newborn infants needing special care (1998)
A prospective study was carried out over a six-month period to determine the pattern and outcome of ocular abnormalities in newborn infants needing special care. All babies at risk of developing retinopathy of prematurity (ROP) were excluded from the study as they were included in a concurrently running ROP study. Twenty-eight of the remaining 84 babies examined were found to have ocular problems. These included retinal haernorrhages which were found in 64 percent of the 28 babies, deeply yellow retinae in 18 percent and retinal oedema in seven percent. Although all the changes encountered resolved by the time the babies were discharged, it is recommended that the eyes of babies admitted into the special care baby unit for whatever reason, should be routinely examined, in order to identify early changes that are amenable to treatment.